Brexit from EU: Lessons for ASEAN? - Mordecai, Aedan (2016)
As the UK prepares for the national referendum on whether to stay in the EU, the British Prime Minister attempts to negotiate reforms to the union. Choosing to leave would have significant consequences for all parties involved. Could ASEAN face a similar situation one day?